2023
DOI: 10.1088/1361-665x/acc1b8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and performance evaluation of a vortex-induced vibration energy harvester with hybrid bluff body

Abstract: To investigate the influence of bluff body with a variable section on the vortex-induced vibration energy harvesting performance, a series of hybrid cylinders are designed and a quantitative comparison is presented. The basic elements of hybrid bluff body are the D-shaped (D) and original circular-shaped cylinders (O), and the length ratio between the O-shaped part and the D-shaped part is fixed. According to the arrangement order, three kinds of hybrid bluff bodies are termed as ODO, ODODO and DOD. A distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the natural environment, the direction and speed of the wind is generally time-varying. Although the cylinder bluff body can induce VIV from all directions thanks to its geometric characteristics, the classical VIV-based harvester with a straight beam as the supporting structure has restrict the direction adaptivity [15,16]. To widen the operational direction range and enhance the output performance, Wang et al [17] and Shi et al [18] proposed the cross-coupled dual-beam VIV energy harvester design in which a cylindrical bluff body was supported by two series-connected beams with bending directions perpendicular to each other, and it can work in two incident wind directions.…”
Section: Introductionmentioning
confidence: 99%
“…In the natural environment, the direction and speed of the wind is generally time-varying. Although the cylinder bluff body can induce VIV from all directions thanks to its geometric characteristics, the classical VIV-based harvester with a straight beam as the supporting structure has restrict the direction adaptivity [15,16]. To widen the operational direction range and enhance the output performance, Wang et al [17] and Shi et al [18] proposed the cross-coupled dual-beam VIV energy harvester design in which a cylindrical bluff body was supported by two series-connected beams with bending directions perpendicular to each other, and it can work in two incident wind directions.…”
Section: Introductionmentioning
confidence: 99%
“…Their experiments results showed that the synchronization regions of the bottom, top, and horizontal configurations are almost the same at low wind speeds, and the vertical configuration has the highest wind speed for synchronization with the largest harvested power. The effect of hybrid bluff bodies on VIV energy harvesting performance has been investigated in Li et al (2023). They considered the hybrid bluff body as a combination of two kinds of bluff elements, that is, O-shaped cylinder and D-shaped prism.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review shows that the main element of piezoelectric energy harvesters are often a cantilever beam with a bluff body in its tip. Therefore, the nonlinear effect due to middle layer stretching effect has been neglected in the previous works (Abdelkefi et al, 2012;Akaydin et al, 2010;Dai et al, 2016;Ewere and Wang, 2014;Gao et al, 2013;Hou et al, 2020Hou et al, , 2022Jia et al, 2018;Li et al, 2022aLi et al, , 2022bLi et al, , 2023Ma et al, 2023;Mehmood et al, 2013;Rezaei and Talebitooti, 2019;Seyed-Aghazadeh et al, 2020;Skop and Griffin, 1973;Sui et al, 2022;Sun et al, 2019;Wang et al, 2020;Yang and He, 2019;Zhang et al, 2022;Zhang and Wang, 2016;Zhao et al, 2012Zhao et al, , 2016Zhao et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%